Framing for the heritage conservation in Malaysia - Abdullah, Karmilah; Ling, Tan Poh; Abdul Rahman, Azlan (Human Resource Management Academic Research Society, 2021)
The public learns about conservation through the media. While mainstream media have been found to not focus on reporting on this issue in the Malaysia, little research has examined how media frame conservation issues. This paper aims to examine the heritage conservation issues in the mainstream newspapers in Malaysia. The management of conservation issue often arise where groups have different goals or priorities leading to the conflicting emphasis on this issue. As such, media can play an important dual role in to offer insights and the various stakeholders perceive shape on the particular issues. Examining media frames of these newspapers in the construction of heritage conservation would identify the perspective of the issue being discussed in the media. This study used framing as the theoretical framework and content analysis as the research method to examine the role of newspaper in constructing heritage conservation identity and the effect in pushing the conservation movement. Data were collected from 2008 to 2018 and it was found that over the 10 years’ period, only 116 articles are covered on this issue. This illustrates that, the media have not put much attention on this issue. The unbalanced media coverage rate over the years sampled suggest opportunities for increased media engagement on this particular issue to further encourage participation of the public towards the conservation and preservation, thus, creating and engaging citizen on these issues are important to best meet the efforts.